2005
DOI: 10.1007/s10549-005-1483-4
|View full text |Cite
|
Sign up to set email alerts
|

GREB1 is a critical regulator of hormone dependent breast cancer growth

Abstract: These data suggest that GREB 1 is critically involved in the estrogen induced growth of breast cancer cells and has the potential of being a clinical marker for response to endocrine therapy as well as a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
239
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(258 citation statements)
references
References 29 publications
19
239
0
Order By: Relevance
“…MCF-7, T47D and BT-474 cells were obtained from the Tissue Culture Shared Resource (TCSR) at the Lombardi Comprehensive Cancer Center and were routinely cultured in modified IMEM (Biosource International Inc., Camarillo, CA) supplemented with 10% fetal calf serum (Valley Biomedical Inc., Winchester, VA), at 37°C in a humidified 5% CO 2 atmosphere. For assays in defined hormone conditions, cells were repeatedly washed and grown in steroid depleted media (phenol red-free IMEM supplemented with 10% charcoal stripped calf bovine serum -CCS) as previously described [14]. For growth assays, cells were plated in steroid-depleted media at 2 × 10 3 cells / well in 96-well plates (Falcon, Lincoln Park, NJ) and allowed to attach overnight before being treating with vehicle control (ethanol 0.1%), E2, androgens, and the steroid antagonists.…”
Section: Methods Cell Lines Culture Conditions and Growth Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…MCF-7, T47D and BT-474 cells were obtained from the Tissue Culture Shared Resource (TCSR) at the Lombardi Comprehensive Cancer Center and were routinely cultured in modified IMEM (Biosource International Inc., Camarillo, CA) supplemented with 10% fetal calf serum (Valley Biomedical Inc., Winchester, VA), at 37°C in a humidified 5% CO 2 atmosphere. For assays in defined hormone conditions, cells were repeatedly washed and grown in steroid depleted media (phenol red-free IMEM supplemented with 10% charcoal stripped calf bovine serum -CCS) as previously described [14]. For growth assays, cells were plated in steroid-depleted media at 2 × 10 3 cells / well in 96-well plates (Falcon, Lincoln Park, NJ) and allowed to attach overnight before being treating with vehicle control (ethanol 0.1%), E2, androgens, and the steroid antagonists.…”
Section: Methods Cell Lines Culture Conditions and Growth Assaysmentioning
confidence: 99%
“…GREB1 mRNA expression was measured using a semi-quantitative real-time PCR assay as described previously [14]. Briefly, total RNA (1µg) was reverse transcribed using Reverse Transcription System (Promega, Madison, WI) and the resulting cDNA amplified in a 25µl reaction containing Platinum Supermix UDG (Invitrogen Corp., Carlsbad, CA), 250 nM of each primer (forward 5′-CAA AGA ATA ACC TGT TGG CCC TGC-3′ and reverse 5′-GAC ATG CCT GCG CTC TCA TAC TTA-3' -Integrated DNA Technologies, Inc., Coralville, IA), 10 nM fluorescein (BioRad Inc., Hercules, CA), and SYBR Green.…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, HPIP levels were higher on TBK1 depletion (Figure 2c). Finally, mRNA levels of GREB1 (growth regulation by estrogen in breast cancer 1), an early-response gene in the estrogen receptorregulated pathway that promotes hormone-dependent cell proliferation, 31 were severely affected on HPIP or TBK1 depletion in estrogen-treated MCF7 cells (Figure 2d). Tamoxifen is a commonly used anti-estrogen therapy for hormone receptor-positive breast cancers, but resistance to this drug occurs through multiple mechanisms, including deregulated AKT activation.…”
Section: Tbk1 and Hpip Regulate Estrogen-mediated Akt Activationmentioning
confidence: 99%
“…We crossed several studies from the recent literature based on microarray transcriptome analyses and ChIP-chip, ChIP-DSL or ChIP-paired end di-tag data obtained from mammary tumor cell lines (Lin et al, 2004(Lin et al, , 2007Laganiere et al, 2005;Kininis et al, 2007;Kwon et al, 2007) to select a group of relevant genes based on the following criteria: hormone-stimulated gene expression in ERa-positive mammary tumor cell lines, complete lack of expression in ERa-negative breast cancer cell lines (Nagaraja et al, 2006) and ERa target identified by ChIP. Thus, we investigated gene regulation of Annexin A9 (ANXA9), a gene coding for a protein of the annexin superfamily (Raynal and Pollard, 1994;Gerke and Moss, 2002), the RET proto-oncogene, which encodes a protein receptor tyrosine kinase with a zinc finger domain associated with dominantly inherited cancer syndromes (Goodfellow and Wells, 1995), the tumor protein D52-like 1 (TPD52L1 (D53)) upregulated in human breast and prostate cancers (Balleine et al, 2000;Ahram et al, 2002;Pollack et al, 2002;Rubin et al, 2004), bone morphogenetic protein-6 (BMP6), a multifunctional molecule of the transforming growth factor-b superfamily overexpressed in breast, prostate and salivary gland cancers (Hamdy et al, 1997;Heikinheimo et al, 1999) and the gene regulated in breast cancer 1 (GREB1), whose product contributes to the growthpromoting effects of estrogens in MCF-7 cells (Rae et al, 2005). We confirmed that expression of these genes was stimulated by estradiol in MCF7 cells (Figure 7a) and assessed changes in relative expression levels in the MDA-66 cells in the absence and in the presence of AZA.…”
Section: Dna Demethylation and Histone Deacetylation Trigger Hormone-mentioning
confidence: 99%